A contingent valuation approach to evaluating willingness to pay for an improved water pollution management system in Dhaka City, Bangladesh - Sehreen, Farhana; Masud, Muhammad Mehedi; Akhtar, Rulia; Masum, Md Razu Ahmad (Springer, 2019)
The city of Dhaka has been ranked repeatedly as the most polluted, the most populous, and the most unbearable city in the world. More than 19.5 million inhabitants live in Dhaka, and the population growth rate of urban areas in Bangladesh is almost double that of rural areas. Rapid urbanization is one of the leading contributors to water pollution in Dhaka and could prevent the country from achieving sustainable development. Therefore, this study estimates respondents’ willingness to pay (WTP) to improve water pollution management systems and identifies factors that influence WTP in Dhaka. This study employed the contingent valuation method (CVM) to estimate WTP of the respondents. Data were collected using a structured questionnaire with CVM questions, which was distributed to households in the study areas. The results revealed that 67% of the respondents are willing to pay for an improved water pollution management system, while 31.8% of households are unwilling to pay. The study also found that socio-economic factors (e.g., income and education) and perception significantly influence WTP. Therefore, this paper will provide directives for policymakers in developing an effective policy framework, as well as sensitize all stakeholders to the management of water pollution in Dhaka. The study suggests that social institutions, financial institutions, banks, non-government organizations (NGOs), insurance companies, and the government could provide effective outreach programs for water pollution management as part of their social responsibility. © 2019, Springer Nature Switzerland AG.